VISUOMOTOR BEHAVIOUR REHEARSAL IN ENHANCING MOTOR ABILITY IN SOCCER PERFORMERS - NURFARAH EZZATY BINTI MOHD ZAHIR,; HUDA FOUJIA,; FARIA SULTANA,; AHMED MARUF,; SAHA, SOUMENDRA, (International Journal of Pharma and Bio Sciences, 2016)
The study was conceived to identify the integral processes involved in Visuomotor behavior rehearsal (VMBR), which involves the psychological aspect of configuration of mental image along with feedback from the performance of the physical skill. Altogether eighty-five young male high performing soccer players volunteered as participants, who were subjected to evaluation of motor skills and abilities pertaining to bidirectional and bilateral coordination and dexterity; inner psychobiological status (autonomic indices of phasic skin conductance response habituation paradigm components). At first participants were subjected to evaluation of psychomotor; psychobiological and soccer skill performance parameters. Thereafter they were introduced to audio-visual analyses of their movement errors. The ideomotor motions characterized by proprioceptive kinesthetic actions in the athletes were monitored and those were clarified to them. Psychobiological evaluations revealed inner core emotional processes substantiating unconscious fear of apprehension related to catastrophic athletic performance. Simultaneous training of VMBR consisted of enhancement in autonomic adaptation followed by the revelation of errors and development of guided imageries to rectify the erroneous components. Outcomes revealed that enhancement in autonomic recovery helped the players to remain more task-focused and to perform optimally at par with the desired standards of psychomotor performance, which evidentially helped them to display enhanced soccer skill performance.